Modelling the Relationship between Rice Price, Rice Production, Exchange Rate, and Rice Import in Indonesia - Yafi, Muhammad Ali; Adyanti, Amanda Sekar; Purwanti, Amanda Anggi (Agro Ekonomi, 2025)
Rice is a strategic food commodity for Indonesia. Most Indonesians, 95 percent consume rice as their staple food. However, Indonesia still imports rice to fulfil its domestic rice needs. Dependence on imports is neither good for the short term nor the long term. The purpose of this study is to see the relationship of rice price, rice production, exchange rate to Indonesia's rice import. The data used is time series data with monthly frequency from January 2019 to December 2023 taken from ITC Trade Map, Central Statistic Agency, and Bank Indonesia. The analysis method uses a Vector Error Correction Model (VECM) approach that can provide short-term and long-term information through several tests. The results showed that in the long run the exchange rate and rice production have a negative influence on rice imports. While in the short term, the variables that affect rice imports are the import variable itself and the price of rice in the previous 2 periods, as well as rice production in 1 previous period. The significant influence of rice production requires the government to pay attention to the stock and the amount of imports in balance. Exchange rate, rice price, and rice production variables respond relatively quickly to rice imports. The rice import variable has a large enough proportion in influencing itself followed by the exchange rate, and rice production which has a greater influence each period.